A Social Network Analysis of HIV Treatment Partners and Patient Viral Suppression in Botswana. (1st June 2018) - Bogart, Laura M.; Mosepele, Mosepele; Phaladze, Nthabiseng; Lekoko, Bright; Klein, David J.; MacCarthy, Sarah; Green, Harold D.
Abstract : Objective: Many national HIV guidelines recommend that health care providers encourage patients to identify a treatment partner from their social network to support antiretroviral therapy adherence. This study examined associations of patient and treatment partner characteristics with patient viral suppression in Botswana. Design: One hundred thirty-one patients [67 (51.1%) virally suppressed and 64 (48.9%) not suppressed] and their treatment partners were recruited for cross-sectional interviews from one HIV clinic. Methods: Participants completed surveys assessing social network, sociodemographic, and psychosocial characteristics. Open-ended questions explored treatment partner relationship quality. Results: Multivariate logistic regressions indicated a higher likelihood of viral suppression among patients who reported greater average emotional closeness to their network members [odds ratio (95% confidence interval) = 3.8 (1.3 to 11.5), P = 0.02] and whose treatment partners were spouses/partners [odds ratio (95% confidence interval) = 2.6 (1.0 to 6.7), P = 0.04]. Qualitative analyses indicated that treatment partners of suppressed patients provided both medical and nonmedical support, whereas treatment partners of unsuppressed patients focused mainly on adherence reminders and appointment accompaniment. Treatment partners, especially of unsuppressed patients, requested ongoing training and counseling skills. Conclusions: Additional research is needed to further explore effective characteristics of treatment partners to inform HIV treatment guidelines. Standard training for treatment partners could include medical-related information and counseling education.